2018
DOI: 10.1016/j.dyepig.2018.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and optical properties of extended TPA-Benzodifuran derivatives connected by cyano-vinylene junctions

Abstract: Two new conjugated molecules based on triphenylaminebenzo [1,2-b:4,5-b']difuran moieties and integrating cyanovinyl bonds have been synthesized by using the new benzodifuran-acetonitrile synthon, easily and rapidly prepared in two steps from 2,2'-(2,5-dihydroxy-1,4-phenylene)diacetic acid. The electronic properties of the molecules were analysed by UV-Vis absorption and emission spectroscopies and cyclic voltammetry. The potential use of the molecules as donor materials for photovoltaic conversion were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The 2-coumaranone was easily prepared in 90 % yield by cyclisation of 2-hydrophenylacetic acid under microwave irradiation. [35,36] Then 2-benzofuran acetonitrile 1 was obtained by the condensation of the stabilized ylide Y on the 2coumaranone. [23] Non classical Wittig reactions of lactones with stabilized ylides can be performed by using forcing conditions like high temperature and/or microwave irradiation.. [37,38,39] The resulting ethylenic derivative is not isolated because undergoing tautomerism rearrangement to afford 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-coumaranone was easily prepared in 90 % yield by cyclisation of 2-hydrophenylacetic acid under microwave irradiation. [35,36] Then 2-benzofuran acetonitrile 1 was obtained by the condensation of the stabilized ylide Y on the 2coumaranone. [23] Non classical Wittig reactions of lactones with stabilized ylides can be performed by using forcing conditions like high temperature and/or microwave irradiation.. [37,38,39] The resulting ethylenic derivative is not isolated because undergoing tautomerism rearrangement to afford 1.…”
Section: Resultsmentioning
confidence: 99%
“…2‐Benzofuranacetonitrile 1 was obtained in two steps from 2‐hydroxyphenylacetic acid by using microwave irradiations as shown in scheme 2. The 2‐coumaranone was easily prepared in 90 % yield by cyclisation of 2‐hydrophenylacetic acid under microwave irradiation [35,36] . Then 2‐benzofuran acetonitrile 1 was obtained by the condensation of the stabilized ylide Y on the 2‐coumaranone [23] .…”
Section: Resultsmentioning
confidence: 99%
“…synthesized two new BDF‐based small molecules SMBDF3 and SMBDF4 via relatively simple routes. [ 266 ] Despite of the OSCs based the two small molecules showed poor efficiency, the insertion of the BDF unit and the extension of the conjugated systems increased fluorescence quantum yield. This study proved that BDF‐based small molecules were potential candidates for organic optoelectronic materials.…”
Section: Benzodichalcogenophene‐based Materials Used In Oscsmentioning
confidence: 99%
“…After recent explorations of facile and efficient synthetic methodologies, BDF derivatives, including small molecules and polymers, have been widely used for high performance organic electronics such as organic photovoltaics ( Li et al, 2010 ; Huo et al, 2012a ; Huo et al, 2012b ; Li et al, 2012 ; Aeschi et al, 2013 ; Li et al, 2013b ; Kularatne et al, 2013 ; Gao et al, 2020 ), organic field effect transistors (OFETs) ( Huang et al, 2014 ; Wang et al, 2016 ; Zhang et al, 2017 ; Wang et al, 2018 ), organic light-emitting diodes (OLEDs) ( Tsuji et al, 2007 ; Tsuji et al, 2009 ; Mitsui et al, 2012 ) and single-molecule devices ( Li et al, 2014 ; Huang et al, 2015 ; Xiang et al, 2015 ; Baghernejad et al, 2020 ). It has been demonstrated that extended π-conjugated BDF derivatives suitably functionalised with either pyridine ( Yi et al, 2010 ), or pyrene and anthracene ( Keller et al, 2011 ) or triphenyl amine (TPA) ( Faurie et al, 2018 ) termini show very strong fluorescence emission with luminescence quantum yields Φ F of up to 0.98. Inspired by these results we have explored new chromophores for high performance OLED applications, utilising the synergetic effect of the BDF core and two TPA substituents linked either through single bonds or double bonds along the long and the short axes ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%